Investigation of hot electron behaviors in plasmonic AgAu@TiO2 nanostructures - Yu, Sijia (2019)
Exploiting plasmonic metal nanostructure is of great importance to achieve highly efficient light-matter interactions. Anisotropic plasmonic metal nanoparticles display excellent optical characteristics from UV, throughout the visible light region to the NIR region of the solar spectrum, which allows high-efficiency conversion of solar energy into chemical energy. Under surface plasmon resonance (SPR) excitation, energetic hot carriers can be generated via dephasing of free electrons oscillation. However, efforts are still needed for better understanding the plasmonic induced hot electrons. In this thesis, several metal/semiconductor hybrid nanostructures based on AgAu core-shell nanoprisms and titanium dioxide were successfully synthesized, photocatalysis efficiencies based on hydrogen generation under visible light were evaluated aim to discover the generation and transfer process of plasmon generated hot electrons. To achieve this goal, the following works have been done. First, for the first time, a Janus nanostructure composed of AgAu nanoprism and titanium dioxide nanosphere was reported. The hybrid nanostructure experience enhanced photocatalytic activity for hydrogen evolution reaction (HER) compare with the conventional metal@semiconductor core-shell nanostructure. The three-phase interphase connecting AgAu nanoprisms, TiO2 nanosphere and environment close the gap between hot electron generation location and photocatalytic reaction site. Moreover, the interface experience largely enhanced electric field along the plasmonic AgAu nanoprisms edges. The site-selective Au nanoparticles photodeposition further confirmed the photocatalysis reaction site on the AgAu/TiO2 Janus nanostructure. Second, facet-selective gold nanoparticles deposition onto AgAu@TiO2 nanoprisms was achieved. Plasmonic metal nanostructures can enhance the local electric field around the nanoparticles under plasmon excitation, the distribution of electric field is closely related to the morphology of the anisotropic nanostructure. To evaluate the relationship between electric field enhancement and hot electron generation distribution, photodeposition of gold nanoparticles on AgAu@TiO2 nanoprisms were performed under irradiation of visible i Abstract